2018
DOI: 10.1371/journal.pone.0199465
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the relationship between the ferritin and homeostasis model assessment of insulin resistance in non-diabetic Korean adults

Abstract: BackgroundThe present study was conducted to assess gender difference in the relationship between the ferritin and homeostasis model assessment of insulin resistance (HOMA-IR) and beta cell function (HOMA-B) in non-diabetic Korean adults.Materials and methodsA sample including 5,414 adults (2,279 men, 1,529 postmenopausal women, and 1,606 premenopausal women) aged ≥ 20 years from the fifth Korean National Health and Nutrition Examination Survey (KNHANES V-1, 2010) was analyzed.ResultsThere were several key fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…High serum ferritin levels increased the risk of moderate/severe periodontitis, and, together with transferrin saturation, increased the risk for higher proportion of sites with CAL ≥4 mm in PM women. This association could be confounded by the higher iron level effects on systemic bone metabolism (Kim et al, 2013), or by insulin resistance and diabetes (Zhao et al, 2012;Yoon et al, 2018) since these factors have been consistently associated with periodontitis (Chapple & Genco, 2013;Penoni et al, 2017). However, the association found by this study was independent of the progressive adjustment for age, years of education, PI, smoking, alcohol, obesity, oestrogen replacement, vitamin D deficiency, low bone mineral density, insulin resistance, and C-reactive protein.…”
Section: Discussionmentioning
confidence: 64%
“…High serum ferritin levels increased the risk of moderate/severe periodontitis, and, together with transferrin saturation, increased the risk for higher proportion of sites with CAL ≥4 mm in PM women. This association could be confounded by the higher iron level effects on systemic bone metabolism (Kim et al, 2013), or by insulin resistance and diabetes (Zhao et al, 2012;Yoon et al, 2018) since these factors have been consistently associated with periodontitis (Chapple & Genco, 2013;Penoni et al, 2017). However, the association found by this study was independent of the progressive adjustment for age, years of education, PI, smoking, alcohol, obesity, oestrogen replacement, vitamin D deficiency, low bone mineral density, insulin resistance, and C-reactive protein.…”
Section: Discussionmentioning
confidence: 64%
“…For example, in a study that examined the relationship between serum ferritin and vitamin D status, 25-hydroxyvitamin D level was inversely associated with ferritin levels in men, but was positively associated with ferritin levels in premenopausal women [ 38 ]. Another study showed that ferritin was positively associated with insulin resistance in men but not in premenopausal women [ 39 ]. Thus, the relationship between ferritin levels and gender seems to be complex and might be modulated differentially under various health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, it has been shown that serum ferritin concentration is connected with fasting plasma glucose, serum insulin concentration (17), and plasma triglycerides (TG) level (18). Additionally, studies revealed that serum ferritin levels are connected with homeostasis model assessment of insulin resistance (HOMA-IR) in a non-diabetic population but not in patients with impaired glucose tolerance (19)(20)(21)(22). Therefore, serum ferritin has been proposed as an early marker of insulin resistance (21).…”
Section: Introductionmentioning
confidence: 99%